2023
DOI: 10.1002/mnfr.202200579
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Alleviate Food Protein Allergy in Mice by Activating TLR4 Signaling Pathway

Abstract: Scope Food allergy has become a world recognized public health problem due to its versatility and lack of efficacious methods for its treatment. Probiotics supplement is a potential way to prevent food allergy. Methods and results In this study, potential strains are screen out by peripheral blood mononuclear cells (PBMCs), and their abilities of alleviating food allergy are examined using a mouse model induced by ovalbumin (OVA). The results show that six strains increase ratio of interferon‐γ (IFN‐γ)/interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In recent study, the activation of the TLR4 pathway by Bifidobacterium animalis KV9 and Lactobacillus vaginalis FN3 also led to modulation of the Th1/Th2 balance, attenuating allergic responses in FA mice [114]. The study demonstrated that KV9 and FN3 possessed anti-allergic activities, they modulated the expression of IRF-1 and IRF-4.…”
Section: Probiotics and Symbioticsmentioning
confidence: 87%
See 1 more Smart Citation
“…In recent study, the activation of the TLR4 pathway by Bifidobacterium animalis KV9 and Lactobacillus vaginalis FN3 also led to modulation of the Th1/Th2 balance, attenuating allergic responses in FA mice [114]. The study demonstrated that KV9 and FN3 possessed anti-allergic activities, they modulated the expression of IRF-1 and IRF-4.…”
Section: Probiotics and Symbioticsmentioning
confidence: 87%
“…Clostridium butyricum, Lactobacillus gasseri and Bifidobacterium species [111][112][113] and Lactobacillus vaginalis [114]: FA animal model.…”
Section: Probiotics and Symbioticsmentioning
confidence: 99%
“…The probiotics also enhanced the IFN-γ/IL-4 ratio in splenocytes and regulated the expression of TLR4, Myd88, and IRF-1 and -4 in the spleen of the allergic mice. The probiotics increased the gene expression of TLR4 and Myd88 and ameliorated FA by stimulating the TLR4 signaling pathway which modulated the T H 1/T H 2 cell immunology [33].…”
Section: Animal Trialsmentioning
confidence: 97%
“…Studies proved that specific strains of probiotics can alleviate symptoms of FA by restoring the imbalanced T H 1/T H 2 immunity through the manipulation of the secretion of cytokines and chemokines towards the T H 1-skewered immunity. X. Tian et al [33] investigated the effects of 41 strains of probiotics on OVAsensitized murine models. Only six strains out of the 41 strains of probiotics have shown positive effects on the alleviation of allergic reactions, which is measured and quantified by the increase in the IFN-γ/IL-4 ratio secreted by human peripheral blood mononuclear cells.…”
Section: Animal Trialsmentioning
confidence: 99%